Nasal High Flow at 25 L/min or Expiratory Resistive Load Do Not Improve Regional Lung Function in Patients With COPD: A Functional CT Imaging Study - Cohen, Julien G.; Broche, Ludovic; Machichi, Mohammed; Ferretti, Gilbert R.; Tamisier, Renaud; Pépin, Jean-Louis; Bayat, Sam (Frontiers in Physiology, 2021)
Background: Nasal high flow (NHF) is a non-invasive breathing therapy that is based on the delivery via a large-caliber nasal cannula of heated and humidified air at flow rates that exceed peak inspiratory flow. It is thought that positive airway pressure generated by NHF can help reduce gas trapping and improve regional lung ventilation. There are no data to confirm this hypothesis at flow rates applicable in stable COPD patients. Methods: In this study, we used non-rigid registration of CT images acquired at maximal expiration and inspiration to compute regional lung attenuation changes (dHU), and lung displacement (LD), indices of regional lung ventilation. Eight COPD patients were assessed at baseline (BL) and after 5 min of NHF and expiratory resistive loading (ERL). Results: dHU was: BL (median, IQR): 85 (67.2, 102.8); NHF: 90.7 (57.4, 97.6); ERL: 74.6 (46.4, 89.6) HU (p=0.531) and LD: 27.8 (22.3, 39.3); 17.6 (15.4, 27.9) and 20.4 (16.6, 23.6) mm (p=0.120) in the 3 conditions, respectively. Respiratory rate significantly decreased with both treatments (BL: 17.3 (16.4, 18.9); NHF: 13.7 (10, 15); ERL: 11.4 (9.6, 13.2) bpm; p<0.001). Conclusions: Neither NHF at 25 L/min nor ERL significantly improved the regional lung ventilation of stable COPD patients with gas trapping, based on functional lung CT imaging. Further study including more subjects is needed to assess the potential effect of NHF on regional lung function at higher flow rates.